Ceramides and Ceramide Scores: Clinical Applications for Cardiometabolic Risk Stratification - Hilvo, Mika; Vasile, Vlad C.; Donato, Leslie J.; Hurme, Reini; Laaksonen, Reijo (Frontiers in Endocrinology, 2020)
Ceramides are bioactive lipids playing an important role in many cellular functions such as apoptosis and inflammation. During the past decade emerging clinical data have shown that ceramides are not only of great biochemical interest but also may add value to clinical diagnostics. As an example, ceramides have shown independent predictive performance for cardiovascular outcomes both in primary and secondary prevention and for the type 2 diabetes onset. Based on wealth of clinical data, easy-to-use ceramide scores have been developed and adapted to clinical use. Currently, it is safe to conclude that serum ceramides are efficient risk stratifiers in cardiovascular diseases (CVD), but their potential causality has not yet been proven. While waiting for ceramide-specific drugs to be developed, more generic lipid lowering treatments such as statins and lifestyle interventions can be used in ceramide lowering. Current clinical applications of ceramide measurements may include for instance identification of very high-risk coronary heart disease patients in need for more intense medical attention, as stated in the 2019 European Society of Cardiology guidelines for stable chronic coronary syndrome patients. In addition, ceramide score may be used as a decision-making tool in patients with moderate CVD risk and in-between LDL-cholesterol levels. Finally, ceramide risk score may be used as a motivational tool in order to increase patient’s adherence to medical therapy and lifestyle changes.